Structural properties of a new class of stellar structures in modified teleparallel gravity - Caliskan, Aylin; Zulqarnain, Rana Muhammad; Güdekli, Ertan; Siddique, Imran; Ahmad, Hijaz; Askar, Sameh (Frontiers in Astronomy and Space Sciences, 2023)
This paper explores new neutron star models based on spherically symmetric space–time. We take into account the gravitational effects of f(T,T) gravity, in which T is the torsion and T is the trace of the energy–momentum tensor. Field equations are evaluated by incorporating the off-diagonal tetrad. In this paper, we discuss the detailed properties of compact star candidates 4U1538–52, J0437–4,715, J0030 + 0451, and 4U1820–30, like energy density, pressure profiles, gradients, anisotropy, energy conditions, equation of state, speeds of sound, TOV equation, and compactification parameters. We discuss all these characteristics using the quadratic cosmological model of f(T,T) gravity. We use the well-famed junction equations to evaluate the unknown parameters. Our detailed and comprehensive graphical analysis ensures that the model containing the anisotropic nature of stellar structures is physically acceptable, regular, and stable.